THE USE OF MODERN TECHNOLOGIES IN TEACHING FOREIGN LANGUAGE SPEAKING IN HIGH SCHOOL - Nazarov Bekhzod Bakhtiyarovich, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The purpose of the article is to illustrate the importance of technologies and technological tools which can be used for teaching and learning a foreign language at high school. Moreover, the article shows some benefits of utilizing technologies and innovative ways during the lesson to teach pupils for integrated skills: reading, writing and grammar.